The mental health trajectories of male prisoners and their female (ex-)partners from pre- to post-release - Souza, Karen; Lanskey, Caroline; Ellis, Sophie; Lösel, Friedrich; Markson, Lucy; Barton-Crosby, Jenni (Criminal behaviour and mental health, 2021)
Background: There are high rates of mental disorders among prisoners. Prisoners are also likely to have difficulties with intimate relationships, perhaps related to the imprisonment, but their mental health may be relevant. There is a dearth of research on intimate relationship qualities and mental health of offenders and their partners over time. Aims: To explore mental health and relationship trajectories among men in prison, and their partners, before the men's release, through a time 6 months post-release, and then again 8 years later, and to test associations between relationship quality and mental health. Method: Data stem from the Economic and Social Research Council (ESRC)-funded longitudinal ‘Families and Imprisonment Research’ (FAIR) project on paternal imprisonment and family resilience. Inclusion criteria for the study were men serving a short- to medium-term prison sentence who were within 4 months of release; with a current or ex-partner with whom they have at least one child; and for whom there were data on mental health and relationship factors during imprisonment, and at 6 months and 8 years post-release. Similar data were also obtained for their (ex-)partners. Results: The main sample comprised 39 men and 39 women who were in the same ‘family set’ for the first two waves, and after 8 years, 26 men and 30 women were retained. Just over 40% of the men and their (ex-)partners each disclosed that they had a mental health problem preceding his release. Proportions fluctuated slightly over time, with some dissonance between self-perceived disorder and self-ratings on a symptoms rating scale. Twenty-nine couples sustained their relationship during the transition between prison and release, but after 8 years, only four remained together. There was little evidence of association between measures of mental health and relationship quality among either the men or their partners. Conclusions: The findings challenge assumptions about the extent to which partners can play fully supportive roles in a former prisoner's transition from institutional life back into the community, as partners are also likely to be experiencing difficulties during this time. Thus, former prisoners and their families should be afforded equal access to support and assistance during offender rehabilitation.
CRIS-Team Scopus Importer:2021-11-12
Keywords: family resilience; mental health; prisoner re-entry/resettlement